The suitability of coconut stick as reinforcement material in vegetable grout block - Tan Wei Kee (2023)
The soil slope easy to meet the failure because of it is weak strength. Shear strength and compressive strength of soil represent the ability of soil to resist imposed forces. In this thesis, a new combination method was developed for stabilization of soil slope which is adding coconut stick in the treated by vegetable grout.